Pengelolaan Program Koin Nahdlatul Ulama Untuk Kesejahteraan Masyarakat - Shofiyah; Fendy, Izmet Muhammad (Al-Musthofa: Journal of Sharia Economics, 2024)
To find out the management of the NU coin program at LAZISNU Ranting for the welfare of the community and to find out the obstacles and solutions for managing the NU coin program at LAZISNU Ranting Drajat, is the aim of this research. This research uses descriptive qualitative research methods, with a case study type, data collection using interview, observation and documentation methods. Meanwhile, to prove the validity of the data using data triangulation, data sources and analysis techniques are used with the steps of data correction, data reduction, data presentation and drawing conclusions. The results of this research show that (1) The management of the NU coin program at LAZISNU Ranting Drajat has implemented management functions, namely planning, organizing, mobilizing and supervising. Planning includes short-term planning, medium-term planning, and long-term planning. Organizing forms administrators and determines their respective tasks and functions, mobilization which includes guidance, coordination, motivation, communication and supervision, including supervision in the collection, distribution and finance sections. The management of the NU coin program is also able to improve the welfare of the community, namely prosperity both in terms of physical, mental and spiritual aspects. (2) the management's obstacles in managing the NU coin program were that the administrator was not present at the time of collecting the cans and counting time, distribution was not on time, and members of the cans did not fill the cans. The management is inactive, and financial reporting is not yet good. The solution is to remind the management before it is time to collect the coin cans and counting time, invite other administrators who can, socialize and motivate the can members, replace the management with other people, and plan to collaborate with institutions to improve the quality of administration and finances.